Assessing the acceptance of UiTM Pahang users towards the implementation of blended learning approach / Azniza Ahmad Zaini...[et.al.] - Ahmad Zaini, Azniza; Noradzan, Haslinda; Hussain, Fazlin Marini; Canda, Roger (Universiti Teknologi MARA Cawangan Pahang, 2014)
This paper discusses the initial investigation on the factors that influence the acceptance of both lecturers and students of the implementation of Blended Learning (BL) approach in Universiti Teknologi MARA (UiTM) Pahang. Blended learning, also known as semi-attendance based learning, offers flexibility of learning and utilizes the technologies in education. About 30% of the total courses of the various programs in UiTM need to be conducted online by June 2013. However, some of the lecturers were afraid that the students would refuse to participate in online learning and some of them lack IT skills so that they might need extra time to prepare their lecture notes online. Self-administered questionnaires were distributed to 86 final year students of Diploma in Computer Science registered for the programming course and 67students of Diploma in Banking registered for the Malaysian economy course during the June-October 2013 Semester to assess their acceptance of the new approach. At the same time, 53 lecturers from various faculties at UiTM Pahang were also involved in the survey using convenience sampling method and the data were then analysed using descriptive statistics. The users’ perception on i-Learn Portal usage for the BL method, as well as the benefits of implementing Blended Learning approach in their teaching and learning process were also identified. The findings reveal that the students could adapt with the BL approach since most of the students were computer and Internet literate and were gradually adapting to the mixed approaches in assessments. Most of the students also agreed that the implementation of Blended Learning should be continued corresponding with the development of technology, but there were some suggestions on the improvement of the Learning Management System (LMS) portal to achieve the benefits that Blended Learning offers either in physical or virtual classrooms. On the other hand, the findings show that majority of the lecturers do accept the implementation of blended learning mode in their teaching and learning process although they are not ready to do so.